Conversão catalítica de alquilaromáticos sobre catalisadores micro-mesoporosos em reator gás-sólido de leito fixo visando à obtenção de olefinas - Rêgo, Ana Carolina Barbosa (2016)
The development of composites micro-mesoporous type appears with the need to obtain new catalytic cracking for cracking petroleum heavy loads studying the characteristics of these new materials formed. On this idea, the aim of this work was to study the synthesis and characterization of micro-mesoporous catalysts and their application in model reaction of conversion of isopropylbenzene in fixed bed continuous flow catalytic microreactor in order to produce olefins. The micro-mesoporous catalysts of (MCM-41 and SM),(HZSM-5/SM andHZSM-5/MCM-41) and(La/HZSM-5/SM and La/HZSM-5/MCM-41) were synthesized by hydrothermal, mechanosynthesis and wet impregnation, respectively. These catalysts were characterized by X-ray diffraction (XRD), nitrogen adsorption at 77K, thermogravimetric (TG), catalytic test through reaction with model molecule and deactivation of the catalysts. Isopropylbenzene (cumeno) was used as model molecule and the conversion to olefins was measured by propylene formation. The X-ray difratogramas indicated that the synthesized catalysts exhibit characteristic peaks of the microporous structure (ZSM-5) and mesoporous structure (MCM-41, SM). For catalysts containing lanthanum, peaks due to the presence of lanthanum oxide were also identified. Thermogravimetric analysis of precursor materials showed the best temperature to remove organic driver of the micro-channels mesostructured. The catalysts showed total area values determined by BET method in the range 468-1459 m2g-1. The deactivation analysis showed that the composites with higher catalytic activity presented increased deposition of coke. The results indicated that the composite catalyst HZSM-5/SM was the most promising in the conversion of cumeno and propene production.